Preventing Postpartum Depression With Mindful Self-Compassion Intervention: A Randomized Control Study. Issue 2 (February 2020) - Guo, Lu; Zhang, Jing; Mu, Liping; Ye, Zhao
Abstract : Abstract: Mindfulness and self-compassion are reported to have a preventive effects on depression and anxiety disorders. In the present study, we aimed to assess the effect of mindful self-compassion intervention on preventing postpartum depression in a group of symptomatic pregnant women. Participants were screened and assigned to the intervention and control groups randomly. A 6-week Internet-based Mindful Self-Compassion Program was used to train the participants. Multiple scales were used to assess depressive and anxiety symptoms, mindfulness, self-compassion, and mother and infant well-being. All assessments were performed at three time points: baseline, 3 months, and 1 year postpartum. Compared with the control group, the intervention group showed significant improvement in depressive and anxiety behaviors. In addition, the intervention group became more mindful and self-compassionate at 3 months and 1 year postpartum. More importantly, both mothers and infants experienced substantial improvement in well-being. Our findings indicate that mindful self-compassion intervention is effective in preventing postpartum depression and promoting mother and infant well-being.